MicroRNA-126 is a regulator of platelet-supported thrombin generation. (17th August 2020) - Zapilko, Veronika; Fish, Richard J.; Garcia, Alix; Reny, Jean-Luc; Dunoyer-Geindre, Sylvie; Lecompte, Thomas; Neerman-Arbez, Marguerite; Fontana, Pierre
Abstract: Circulating microRNA (miRNA) expression profiles correlate with platelet reactivity. MiR-126 is a promising candidates in this regard. We generated a transgenic zebrafish line with thrombocyte-specific overexpression of miR-126. Laser injury of the posterior cardinal vein of 5 day-old larvae was performed with or without antithrombotic pre-treatment. Platelet-like structures (PLS) derived from human megakaryocytes transfected with miR-126 were also evaluated for procoagulant activity. Finally, we studied the correlation between miR-126 level and thrombin generation markers in a cohort of stable cardiovascular patients. Control zebrafish developed small thrombocyte-rich thrombi at the site of vessel injury, without vessel occlusion. The miR-126 transgenic line developed an occluding thrombus in 75% (95% CI: 51–91%) of larvae. Pre-treatment with the direct thrombin inhibitor argatroban, but not aspirin, prevented vessel occlusion in the transgenic line (0% occlusion, 95%CI: 0–18%). Upon activation, human PLS showed an increased procoagulant profile after miR-126 transfection compared to control. Finally, the plasma levels of miR-126, but not a control platelet-derived miRNA, correlated with markers of in vivo thrombin generation in a cohort of 185 cardiovascular patients. Our results from three complementary approaches support a key role for miR-126 in platelet-supported thrombin generation and open new avenues in the tailoring of antithrombotic treatment.